New records of the family Cucumariidae (Holothuroidea: Dendrochirotida) for the Mexican Pacific - Sánchez-Alonzo, Daniel-M. (2021)
Introduction: Cucumarids are a cosmopolitan group of sea cucumbers that inhabit rocky-sandy sediments, from the intertidal zone to the hadal zone. Objective: To present new records for the Mexican Pacific. Methods: We applied stereoscope and scanning electron microscopy to external and internal morphology of specimens in the collection of the National Autonomous University, Mexico. Results: We present a taxonomic synopsis of cucumarids in the Mexican Pacific and review their taxonomy on the ossicles. The taxonomic identity of Pseudocnus curatus, Pseudocnus dubiosus and Pseudocnus lubricus is confirmed, and the presence of Trachythyone peruana is ruled out. Conclusions: Four new records are presented for the Mexican Pacific: Leptopentacta nina, Pseudocnus curatus, Pseudocnus dubiosus and Pseudocnus lubricus.